"Fathers' Rights" Activism, Discourse, Groups and Impacts: Findings from a Scoping Review of the Literature. Issue 5 (4th July 2019) - Alschech, Jonathan; Saini, Michael
ABSTRACT: The fathers' rights movement emerged in its current form in the 1980s as a decentralized, transnational, grassroots network of activists, support groups, and public polemics concerning child custody and child support laws and policies in the context of separation and divorce. This scoping review reports on existing research on the fathers' rights movement to provide a comprehensive roadmap of how the fathers' rights movement has so far been understood and interpreted in terms of its characteristics and its impacts. Implications include specifying suggestions for future research as well as the implications for practitioners working with separated fathers and their families.